تطوير خوارزمية لتحديد موقع مرسل لاسلكي باستخدام الهوائيات غير الموجهة - علي مسعود (Latakia University Journal -Engineering Sciences Series, 2017)
ناقش هذا العمل طريقة استخدام نظام تحديد الموقع GPS بحجم صغير ورخيص، مع مقياس شدة الحقل وحاسوب شخصي، لتحديد الموقع الجغرافي لمرسل إشارة راديوية متعاون بسرعة وبفاعلية، وهذا التحديد له مجال واسع في التطبيقات العسكرية والمدنية. يمكن تحديد الإحداثيات الجغرافية لمرسل بمساعدة مراقب متحرك، يستقبل الإشارات الواردة من المرسل من مواقع مختلفة. اشتقت العلاقات التحليلية لحساب موقع المرسل المكتشف من أربعة مواقع جغرافية مختلفة باستعمال الجبر الخطي أو طريقة المدى الزائف، تم بناء نموذج رياضي ثم استخدام الـ MATLAB لحل المعادلات الرياضية الناتجة، ونمذجة طريقة تحديد المواقع ورسمها على خريطة جغرافية . This work discusses the feasibility of applying a small and inexpensive GPS, a Field Strength Meter (FSM) and a personal computer, that can activity and rapidly determine the Geo-locations of RF cooperated emitter, which have a wide range of both military and civilian applications. The emitter’s Geo-coordinates can be estimated by a single moving observation system, which receives signals from the emitter, and measures his Geo-locations and Field Strengths of the transmitted signal at four Positions Analytic Formulas are derived to calculate the location of Emitter, which detected from four Positions by using of Linear Algebra or pseudo range’s solution, The MATLAB was used to solve the four Equations and to simulate the Geo-Positions on Geo-Map.